Potential effect of green tea extract for adjuvant treatment of acute ischemic stroke by s100íŸ upregulation in non-thrombolysis patient - Machin, Abdulloh; Suprapto, Djoko Agus; Hanifah, Anny; Suharjanti, Isti; Shodiq, Jakfar; Fatihuddin, M Fata; Kim, Beom Joon; Firdha, Azizah Amimathul (Jurnal Ners, 2023)
Introduction: In ischemic stroke, the cerebral cortex suffers from hypoxia-ischemia, leading to inflammation and oxidative stress. Green tea extract has an anti-inflammation effect and antioxidant. This study aimed to determine the efficacy of green tea extract for adjuvant treatment of acute ischemic stroke in non-thrombolysis patients. Methods: A double-blind randomised controlled trial was conducted in November 2020-November 2021. The subjects were all acute ischemic stroke patients who presented to the Emergency Room during recruitment, randomised into control (n=13) and intervention groups (n=18); the intervention groups were given green tea extract 350 mg. Treatment was for 30 days. National Institutes of Health Stroke Scale (NIHSS), modified Rankin Scale (mRS), Montreal Cognitive Assessment - Indonesia (MoCAIna), IL-10 and S100íŸ were analysed. Results: Data were compared with a significance level of p<0.05. The differences in NIHSS from day 0 to 7, day 0 to 14 and day 0 to 30 were statistically significant in the intervention group (p=0.019, p=0.002 and p=0.000, respectively). The mRS score was statistically significant in the intervention group on day 30 (p=0.46). The differences in mRS score from day 0 to 14 and day 0 to 30 were statistically significant (p=0.042 and p=0.001, respectively) The S100íŸ were statistically significant in day 7 (p=0.006). The difference in S100íŸ from day 0 to 7 was statistically significant (p=0.001).Conclusions: The green tea extract, through up-regulation S100íŸ, can improve the clinical outcomes of acute ischemic stroke.